Digitalization of Cashiering: An Exploratory Study of Students' Experiences in Developing Problem-Solving Skills - Hasan, Imam; Fauzi, Arief Zul (Journal of Economics Education and Entrepreneurship, 2025)
This research aims to find out students' experiences in developing problem-solving skills through making cashier digitalization in MSMEs with a Problem-Based Learning (PBL) approach. This research uses a qualitative method with an exploratory study approach, where data is collected through interviews, observations, and documentation, and then analyzed using the Miles and Huberman model. The results showed that students were able to identify problems faced by MSMEs, design technology-based solutions, and collaborate in developing a system that suits user needs. The learning process through PBL also encourages students to think critically, improve analytical skills, and hone cooperation skills in solving technical challenges. This research shows that the application of PBL in the Accounting Information Systems course not only helps students understand concepts theoretically but also be able to implement them in the real world. Thus, the digitalization of cashiers not only provides benefits for MSMEs in increasing the efficiency of recording transactions but also becomes an effective learning tool for students in honing problem-solving skills.